PUSAT PERDABAN ABAD XV-XVIII KERAJAAN BUKI SELAYAR SULAWESI SELATAN - nfn Muhaeminah; M. Irfan Mahmud (WalennaE, 2009)
The center of Kingdom of Buki was known as a teritory of a powerfull dinasty and reaches their golden age in XV to XVI century based on the foreign ceramics population found. In the next centuries, Buki was still became a powerful dinasty when the Islamic influence spread stronger in XVIII century. At the top of Islamic influence's glory, there was a control to the Silolo site's area that located in the east side of the Kingdom of Buki. But the site of Buki was a still a center for the elite of the kingdom. Buki, Selayar is quite interesting for a research to get a more accurate data. There is several finds like, Maros point (serration arrow point) that found in Batang Mata Sappo area, human skull from Batu Tumpa cave at Bonto Sikuyu, and many other finds. These kinds of finds commonly found in South Sulawesi but Selayar is placing an important position based on the quantity and the quality of its finds.Pusat Kerajaan Buki dikenal sebagai wilayah dinasti yang kuat dan mencapai zaman keemasan mereka di abad XV - XVI berdasarkan populasi keramik asing yang ditemukan. Pada abad-abad berikutnya, Buki masih menjadi kerajaan yang kuat ketika pengaruh Islam menyebar lebih luas di abad XVIII. Pada puncak kejayaan pengaruh Islam, ada kontrol terhadap area situs Silolo yang terletak di sisi timur Kerajaan Buki. Tapi situs Buki masih menjadi pusat elit kerajaan. Buki, Selayar cukup menarik untuk sebuah penelitian untuk mendapatkan data yang lebih akurat. Ada beberapa temuan seperti, maros poin (mata panah bergerig) yang ditemukan di daerah Batang Mata Sappo, tengkorak manusia dari gua Batu Tumpa di Bonto Sikuyu, dan banyak temuan lainnya. Temuan semacam ini umumnya ditemukan di Sulawesi Selatan tetapi Selayar menempatkan posisi penting berdasarkan kuantitas dan kualitas temuannya.